Análisis de la promoción de los eventos culturales, a través de las redes sociales facebook y twitter organizados por el gobierno autónomo descentralizado municipal de Loja. estudio de caso año 2016. - Guaman Tacuri, Maria Jose (2018)
The present investigative work focuses on analyzing the promotion of cultural events, through social networks: facebook and twitter organized by the Decentralized Municipal Government of Loja. The objectives are to know the cultural events organized by the institution, identify what elements and genres are used for their promotion and analyze the reception that the public has. This research has a review of the literature, where are the concepts necessary for this work; then the results for which three research instruments were applied. The first was the surveys with which it was learned that the promotion in social networks carried out by the institution does not influence the attendance of the citizens to cultural events, since they end up being informed by friends, the participation of acquaintances in the events or by traditional media. With the second tool that were the observation cards, it was possible to know the little use that is given to the tools provided by social networks Facebook and Twitter, perhaps due to ignorance of the use of the tools that these social networks have for a correct cultural promotion, which in the end makes the cultural promotion fail. Following the interviews, the opinion of people related to the Decentralized Municipal Government of Loja and specialists of the topic was known, who stated that there should be a greater promotion to cultural events on social networks, so that citizens can enjoy them. After the discussion is shown where the results are compared with the objectives, then the elaboration of the conclusions and recommendations. Finally, a Social Media Plan for the promotion of cultural events is included as a proposal.